Tumor- and Osteoblast-Derived Periostin in Prostate Cancer bone Metastases - Sun, Chuan-Yu; Mi, Yuan-Yuan; Ge, Sheng-Yang; Hu, Qing-Feng; Xu, Ke; Guo, Yi-Jun; Tan, Yi-Fan; Zhang, Yang; Zhong, Fan; Xia, Guo-Wei (Frontiers in Oncology, 2022)
Exploring the biological function of periostin (POSTN) in prostate cancer (PCa) bone metastasis is of importance. It was observed that the expression of POSTN was high in PCa, especially highest in PCa metastasized to bone. In this study, we found that inhibiting POSTN in PCa cells could significantly alleviate PCa bone metastasis in vivo, suggesting POSTN is a promising therapeutic target. Since, due to the secreted expression of POSTN in osteoblasts and PCa, we hypothesized the positive feedback loop between osteoblasts and PCa mediated by POSTN in PCa bone metastasis. The in vitro experiments demonstrated that osteoblast-derived POSTN promoted PCa cell proliferation and invasion and PCa cell-derived POSTN promotes proliferation of osteoblasts. Furthermore, we found that POSTN regulated PCa and osteoblast function through integrin receptors. Finally, 18F-Alfatide II was used as the molecule probe of integrin αvβ3 in PET-CT, revealing high intake in metastatic lesions. Our findings together indicate that targeting POSTN in PCa cells as well as in the osteoblastic may be an effective treatment for PCa bone metastasis.